تأثير التسميد بالبوتاسيوم والمادة العضوية في النمو والصفات النوعية لثمار التفاح صنف ستاركنغ ديلشس (Starking Delicious) وبعض خصائص التربة في محافظة السويداء - خليل, نديم; مزهر, بيان; كيوان, سامر (Latakia University Journal -Biological Sciences Series, 2017)
نفذ البحث في مركز البحوث العلمية في السويداء بهدف دراسة تأثير إضافة البوتاسيوم والمادة العضوية في بعض خصائص التربة وبعض الصفات النوعية لثمار التفاح صنف ستاركنغ ديلشس. أظهرت نتائج تحليل التباين في الأفق (0 – 30 سم) تأثير معنوي في خفض درجة (pH) التربة لمعاملات إضافة كبريتات البوتاسيوم والمادة العضوية وإضافتهما معاً (6.608) و(6.708) و(6.558) على الترتيب بالمقارنة مع الشاهد (6.768)، كما بينت فروق معنوية في الـ (EC) بين المعاملات السابق ذكرها (ds/m0.1532) و(ds/m 0.1692) و(ds/m 0.0937) بالمقارنة مع الشاهد (ds/m 0.2217)، وبينت النتائج زيادة معنوية في طول الطرود في المعاملات السابقة (66.43سم) و (77.33 سم) و(71.37 سم) على الترتيب مقارنة بالشاهد (59.37 سم)، في حين أظهرت زيادة معنوية في مساحة الأوراق في معاملتي إضافة المادة العضوية وكبريتات البوتاسيوم والمادة العضوية معا (35.54سم2) و(37.21 سم2)على الترتيب مقارنة بالشاهد (30.54 سم2). كما بينت نتائج تحليل التباين تفوق معاملة البوتاسيوم في صلابة الثمار التي بلغت (8.477 كغ / سم2) على كافة المعاملات. وكانت الزيادة معنوية في النسبة المئوية للمواد الصلبة الذائبة في المعاملات الثلاث (16.82%) و(15.2%) و(15.37%) بالمقارنة مع الشاهد (14.23%)، وزيادة معنوية في نسبة السكريات الكلية والنسبة المئوية للحموضة. وبالنتيجة تبين أن إضافة هذه المركبات ساهم في تحسين بعض خواص التربة وقوة نمو الأشجار وبعض الصفات الكمية والنوعية لثمار التفاح.This study was carried out at the Agricultural Scientific Research center In Sweida -GCSAR to study the effect of potassium sulfate and organic manure on some of soil characteristic in addition to tree growth vigor and fruit traits of Starking delicious apple cultivar. The results revealed significant effect in reducing the (pH) of the soil in the three treatments; potassium sulfate fertilization, organic manure fertilization and application of potassium sulfate and organic manure together which were (6.608), (6.708) and (6.558), respectively, in the comparison with the control (6.768). In addition, significant differences were shown in the (EC) between the former treatments (0.1532 ds / m), (0.1692 ds / m) and (0.0937 ds / m) compared to the control (0.2217 ds / m). Concerning growth vigor and fuit traits, the results showed a significant increase in the average of shoot length in the previous treatments (66.43, 77.33 and 71.37 cm, respectively), compared to the control (59.37 cm), while showed a significant increase in leaf area in organic manure treatment and potassium sulfate with organic manure together (35.54 and 37.21 cm 2, respectively), compared to the control (30.54 cm 2). The results of analysis of variance in fruit firmness showed higher significant variation of potassium treatment (8.477 kg / cm 2) than the other treatments which, also revealed significant increase of total soluble solids (16.82%,15.2% and15.37%,respectively) compared to the control (14.23%), and a significant increase in total sugars and in percentage of treatable acidity. Consequently, the result showed that the addition of soil fertilizers treatment contributed to improve some of soil characters, tree growth vigor and some of the quantitative and qualitative traits of apple fruits.